Lípidos Alternativos en la Nutrición de Peces Marinos | Alternative Lipids in Nutrition of Marine Finfish - Nishioka Rombenso, Artur (Facultad de Ciencias Biologicas, 2017)
The current paper provides new knowledge regarding LC-PUFA requirements of marine carnivorous fish(White Seabass Atractoscion nobilis, California Yellowtail Seriola dorsalis and Florida Pompano Trachinotuscarolinus) in the context of C18 PUFA-rich and SFA- and MUFA-rich alternative lipids. Determine if all LCPUFAs(ARA, EPA, DHA) are equally important in meeting fatty acids requirements and also determine theeffects of dietary SFA, MUFA, and C18 PUFA content in fish oil sparing and tissue deposition of LC-PUFAs.The overall findings highlighted that DHA and ARA appear to be the primary drivers of fatty acidessentiality, whereas EPA is likely required in minor amounts. It was also demonstrated that DHA/EPA ratiohad little-to-no effect on fish performance. Additionally, LC-PUFA requirements seem to be more flexiblethan previously assumed being influenced by dietary fatty acid profile. LC-PUFAs in marine finfish are morebioavailable in the context of SFA-/MUFA-rich alternative lipids, thus, reducing the requirements for thesenutrients and allowing the fish’s physiological demand to be met with dietary levels below the minimumlevels recommended. Finally, these findings suggest that although marine fish accept a variety of alternativelipids, those rich in SFAs and/or MUFAs seem advantageous in terms of limiting the effects of fish oil sparingon tissue fatty acid profiles.